Serum gastrin levels in patients with colorectal cancer - Ahmet UYGUN,; Can UYGURER,; Namık K. NAZAROĞLU,; Cengiz KAYHAN,; Ergun SARAÇOĞLU,; Celalettin ÇETİN,; Necmettin KARAEREN, (Turkish Journal of Gastroenterology, 2019)
-